The effect of increasing meat price to fresh fish consumption in complex pt.rapp town site ii east kerinci, pelalawan, riau. - Barus, Sri Yantini; Ramli, Mohammad; Nugroho, Firman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research wasconducted on May 2013 in Town Site II of complex PT.RAPP East Kerinci, Pelalawan Province of Riau. The purpose of this research was: 1) Knew the effect of rising prices of meat on fresh fish consumption in complex PT.RAPP Town Site II in Pangkalan Kerinci. 2) Determined corelation of fresh fish and meat consumption, is it complementary or substitution. This research conducted by used survey method with data collection techniques though questionnaire for selected respondents and respondent consist of four groups, with 69 Foreman,12 Supervisor, 8 AssistantManager, 11 Supertendent and total 100 group of family. The effect of rising meat price influenced amount of fresh fish consumption before and after rising price of meat. Fish consumption is likely to increase from 520 Kg to 822 Kg.The fresh fish was become subtitute of meat which mean increased of meat price also increased fresh fish consumption and meat consumption was decline. Key words : Meat Price, Fresh Fish, Consumption